2019
DOI: 10.3389/fphar.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Suppresses Hypopharyngeal Cancer Growth by Epigenetically Silencing Long Non-coding RNA SNHG7 in FaDu Cells

Abstract: Local recurrence after therapy remains a challenging problem for hypopharyngeal cancer (HPC) due to the chemotherapy resistance. Metformin is associated with reduced cancer risk through promoting global DNA methylation in cancer cells by controlling S -adenosylhomocysteine (SAHH) activity. However, the mechanisms by which metformin inhibits HPC remain elusive. In this study, we aim to investigate the role of metformin in HPC and illustrate the mechanism by which metformin regulates long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…It has been reported that metformin can be used to treat diseases through the regulation of lncRNA expression. 43,44 Because metformin was found to attenuate TUG1 expression in a time-dependent manner in the present study, we further investigated its correlation with TUG1 expression. Figure 6 Anti-atherosclerosis (AS) effects of metformin and lncRNA TUG1 in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that metformin can be used to treat diseases through the regulation of lncRNA expression. 43,44 Because metformin was found to attenuate TUG1 expression in a time-dependent manner in the present study, we further investigated its correlation with TUG1 expression. Figure 6 Anti-atherosclerosis (AS) effects of metformin and lncRNA TUG1 in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the expression of SNHG9 was upregulated in GBM, thus it was assumed that SNHG9 may also be a potentially carcinogenic lncRNA. Moreover, it was found that the four lncRNAs were hypomethylated, and one lncRNA (SNHG7) has been reported to improve the survival of patients with hypopharyngeal cancer by inhibiting the hypomethylation of its promoter (56). Furthermore, two MlncBTs (SNHG16-HEATR1 and SNHG16-MUL1) were associated with a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BDNF expression was significantly increased in TC tissues and exhibited a positive correlation with SNHG7 expression. Recently, Wu et al ( 63 ) reported that the expression levels of SNHG7 were elevated in hypopharyngeal cancer (HPC) tissues and were repressed by metformin. Moreover, HPC patients with high SNHG7 expression exhibited a significant correlation with increased tumor size, lower differentiation, lymph node metastasis, distant metastasis, advanced TNM stage, lower overall survival time and resistance to taxol.…”
Section: Snhg7 Dysregulation In Human Cancersmentioning
confidence: 99%